1988
DOI: 10.1177/001440298805500304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Intervention on Hearing Impaired Children

Abstract: A longitudinal study was conducted of 118 children with severe and profound hearing losses-Children were first tested when they were between 3 and 5 years and again in 3 or 4 years, using measures of receptive and expressive spoken language, receptive language in the child's primary educational modality, receptive and expressive mother-child communication, and social development. A multivariate design was used to investigate the effects of age of intervention, program intensity, and parent instruction on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
2
8
1
Order By: Relevance
“…Findings indicated that the early intervention programs developed for the children who had a hearing loss and were living in a rural area of Turkey were effective in the improvement of verbal communication skills of the children and in providing information to parents according to their needs. These findings are similar to findings of previous research indicating that programs prepared according to the characteristics and needs of families were successful (Akcamete & Kargin, 1996j Kargin & Akcamete, 1997Musselman et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…Findings indicated that the early intervention programs developed for the children who had a hearing loss and were living in a rural area of Turkey were effective in the improvement of verbal communication skills of the children and in providing information to parents according to their needs. These findings are similar to findings of previous research indicating that programs prepared according to the characteristics and needs of families were successful (Akcamete & Kargin, 1996j Kargin & Akcamete, 1997Musselman et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…One study however, found that the initial benefits of early intervention on receptive language did not persist; however, the number of children in this study who were identified in the first 6 months of life was likely to be few, if any. 21 Overall this research supports the view that these children (particularly those with more severe impairments) have poor outcomes at present compared with children with normal hearing. Earlier identification is associated with better language acquisition and communication.…”
Section: Impairmentsupporting
confidence: 76%
“…However, as home-based services most often focus on parents, it is difficult to disentangle the effect of the two components (setting of intervention versus parental involvement). Increasing the intensity of the services does not seem to result in better outcomes (Musselman et al, 1988;Innocenti & White, 1993;Taylor, White & Kusmirek, 1993). Similarly, parental compliance to recommended homework procedures does not appear to be associated with better outcomes (Musselman et al, 1988).…”
Section: Achievement Of Hearing-impaired Childrenmentioning
confidence: 94%
“…Increasing the intensity of the services does not seem to result in better outcomes (Musselman et al, 1988;Innocenti & White, 1993;Taylor, White & Kusmirek, 1993). Similarly, parental compliance to recommended homework procedures does not appear to be associated with better outcomes (Musselman et al, 1988). Finally, the conditions under which the programs may produce better results remain largely unknown and, in addition, the efficacy of early intervention may vary depending on child characteristics and the child's environment (Guralnick, 1994 Very few studies have addressed these issues simultaneously and none has yet investigated the effect of the nature of the services provided, their target and the coordination mechanisms on early intervention outcomes.…”
Section: Achievement Of Hearing-impaired Childrenmentioning
confidence: 97%
See 1 more Smart Citation